Awake Thoracotomy in an Obese Case of Cardiac Tamponade: A Case Report - Malek Itmaiza; Peter Bael; Talha Isayed; Ali Abufarah; Islam Frijat; Majdi Hamamdeh (Case Reports in Anesthesiology)
Discussion: We presented the first case to our knowledge that employed parasternal and serratus anterior blocks as local analgesia for an awake thoracotomy, we also discussed different techniques, indications, benefits, and complications.